Mobile Endoscopy vs Video Tower: A Prospective Comparison of Video Quality and Diagnostic Accuracy. (22nd July 2016) - Liu, Hao; Akiki, Salwa; Barrowman, Nicholas J.; Bromwich, Matthew
Abstract : Objective: To determine if any significant difference exists between endoscopic videos captured with a mobile adaptor and videos captured with a traditional tower. Study Design: Prospective controlled blinded comparison of mobile endoscopic videos captured through 2 methods. Methods: Thirty randomly selected patients underwent video endoscopy with both mobile and video tower recording methods. Sixty videos were edited into a series of 10‐second clips. Thirteen otolaryngology staff and residents rated the video quality and provided a diagnosis for each video. Results: We found no significant difference in the video quality ratings between mobile and tower videos (mean difference, −0.07; P <. 37). Similarly, we found no significant difference in the observers' diagnostic accuracy (mean difference, 1.54%; P <. 686). Conclusion: With adequate power, our study was unable to demonstrate a difference between mobile adapter videos and tower videos. Our findings suggest that mobile adapter videos may reasonably be used in lieu of tower videos in clinical practice.